口蓋に発生したpleomorphic lipomaの1例 - 梅木, 泰親; 寺田, 知加; 戸田, (徳山) 麗子; 杉山, 尚希; 佐藤, 徹; 里村, 一人 (日本口腔外科学会雑誌, 2019)
A pleomorphic lipoma is a rare benign lipomatous tumor that has been defined by Enzinger as a new lipomatous entity. Pleomorphic lipoma mainly arises in the subcutaneous tissue of the neck and shoulders in elderly men, with relatively few reported cases of the tumor in the oral maxillofacial region. We report a case of pleomorphic lipoma arising in the left hard palate mucosa of a 67-year-old man. The lesion was a tender, sharp and pedunculated mass measuring 7 × 7 mm. The tumor was surgically removed including the surrounding normal tissue, and the histopathological diagnosis was pleomorphic lipoma. Microscopic examination histologically revealed a subepithelial admixture of mature adipose tissue and overgrowth of fibrous tissue, scattered with CD34-positive large and multinucleated cells. Four years after surgery, the patient remains recurrence-free and has a good clinical course.